A Structure Analysis for Ecological Management of Moist Tropical Forests - Adrien Djomo Njepang (International Journal of Forestry Research)
Human interventions alter stand structure, species composition, and regeneration capacity of the forest. There is no enough information on how different management systems affect the forest structure. The main objective of this study was to analyze the differences on stand structure and species composition caused by different logging intensities. The study was conducted in a lowland evergreen moist forest of 22 000 ha in Cameroon. The forest was subdivided into three forest types with different human impacts: 2-Logged, 1-Logged, and Unlogged. The diameter corresponding to mean basal area of stems of 2-Logged (31.8 cm, N=369) was almost equal to that of Unlogged (30.1 cm, N=496). 1-Logged had a lower diameter of 27.7 cm, N=530. In the three forest types, the diameter distribution followed the inverse J-shaped curve frequently observed in natural forests. The stand basal area increased from 29.4 m2/ha in 2-Logged, to 32 m2/ha in 1-Logged, and to 35.3 m2/ha in Unlogged. These results indicated that logging affected natural regeneration in 2-Logged. Above 60 cm dbh, the logging effect was not visible. On 103 tree species found in the sample forest, only nine were classified as harvestable commercial species.